2017
DOI: 10.1039/c7dt00875a
|View full text |Cite
|
Sign up to set email alerts
|

Ag@Au nanoprism-metal organic framework-based paper for extending the glucose sensing range in human serum and urine

Abstract: In this work, we present a Ag@Au nanoprism-metal-organic framework-paper based glucose sensor for rapid, sensitive, single-use and quantitative glucose determination in human serum. To achieve painless measurement of glucose with a non-invasive detection methodology, this biosensor was further tested in human urine. In this approach, a new hybrid-Ag@Au nanoprism loaded in close proximity to micrometer sized coordination polymers as phosphorescent luminophores significantly enhanced the emission intensity due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Colorimetric analysis is a method to determine the content of a substance to-be-measured by the color of the solution that features good stability, low cost, and implementation simplicity, making it widely applied to clinical diagnosis and detection, including in glucose analysis [3,[6][7][8]. However, current liquid colorimetry primarily requires lab-based infrastructure, and its utility greatly increases the use of point-of-use deployment.…”
Section: Introductionmentioning
confidence: 99%
“…Colorimetric analysis is a method to determine the content of a substance to-be-measured by the color of the solution that features good stability, low cost, and implementation simplicity, making it widely applied to clinical diagnosis and detection, including in glucose analysis [3,[6][7][8]. However, current liquid colorimetry primarily requires lab-based infrastructure, and its utility greatly increases the use of point-of-use deployment.…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced with permission. [ 202 ] Copyright 2017, Royal Society of Chemistry. b,c) Schematic illustration of glucose monitoring in the brain of living rates based on INAzyme, and the schematic illustration of the integrated system along with cascade reactions mechanism for the detection of glucose in living brain.…”
Section: Mof‐based Wearable and Flexible Glucose Sensorsmentioning
confidence: 99%
“…For example, AuNRs, Ag, and AuNCs have rod-shaped, triangular-shaped, and nano-crescent structures, respectively. These structural features are used for tuning the LSPR characteristics over a wide range of wavelengths from visible to NIR, including the transparent biological window by adjusting the aspect ratio [28,[88][89][90]. Therefore, anisotropic structures have great potential to be applied for constructing a highly sensitive MEF system for biological sensing.…”
Section: Metal Enhanced Fluorescence From Nano-particles and Nanoclusmentioning
confidence: 99%
“…Ji et al [ 106 ] fabricated zigzag structures, as shown in Figure 4 a, by employing OAD, and reported a 28-fold EF for Alexa 488 detection with a 0.01 pM detection limit. Although anisotropic nanorods made with other methods were previously reported [ 85 , 89 ], Ji’s work has put forward a pathway for deposition experts in fabricating the MEF-based biosensor using deposition methods. The plasmonic response from such structures can be tuned by controlling the size of nanostructures, which helps to overlap the SP characteristics with the excitation of fluorophores.…”
Section: Metal Enhanced Fluorescencementioning
confidence: 99%